Analysis of Influence Transformational leadership, work motivation on Performance of State-Owned Enterprises Employees in Bali - Putri, Ni Putu Timor Sukardika Eka; Merta, I Ketut; Yusnimi, Ni Made (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This researchaims to examine the influence of transformational leadership and work motivation on the performance of State-owned Enterprises (SOEs) employees in Bali using the grand theory of Human Resources Management (HR). This research uses quantitative methods associative,and a questionnaire with a population of 637 and a side sample of 86, the questionnaire uses the Slovin formula with four hypotheses assisted by data processing with SPSS Version 24. The research results found : 1. Transformational leadership positive and significant effect on work Motivation, 2. Transformational leadership has a significant positive effect on employee performance 3. Work motivation has a positive and significant effect on employee Performance, 4 Work motivation is able to mediate Transformational leadership on employee Performance. Research Implications this results in the influence of transformational leadership, Employee Performance, work motivation in SOES in the Province being quite moderate and shows that Work motivation can mediate Transformational leadership in Employee Performance.